COMPARATIVE ANALYSIS OF CONDUIT STRUCTURE QUANTITY TAKE-OFF USING BUILDING INFORMATION MODELING (BIM) AND CONVENTIONAL METHODS : A CASE STUDY OF CABEAN DAM, BLORA REGENCY - Jannata, Bhagyawan Rizqol Rizqol; Putri Anggi Permata Suwandi; Ikhwanudin; Muslimin; Firmansyah Maulana (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
Quantity Take-Off (QTO) calculation is a crucial element in construction cost management. Conventional methods based on 2D drawings are often prone to interpretation errors and human error, resulting in inaccurate cost estimates. This study aims to evaluate the effectiveness of implementing Building Information Modeling (BIM) in performing QTO for the Diversion Conduit structure at Cabean Dam, Blora Regency. The research method involved remodeling the conduit design using Autodesk Revit 2025 software to obtain concrete volume and reinforcement weight, which were then compared with conventional calculation results and field realization data. The results showed that the BIM method produced more efficient volumes compared to the conventional method. In concrete work, the BIM volume was 1.03% lower than the conventional method, while in reinforcement work (deformed bars), BIM was 7.35% more efficient. When compared with field realization data, the BIM volume represented the net quantity, with an average difference of 0.6% for concrete and 3.5% for reinforcement, representing the waste factor. This study concludes that BIM offers higher accuracy and minimizes project budget over-estimation.